Shared vision and organizational commitment: a case study at EMBRACON – empresa brasileira de consórcios - Leite, Ana Maria Andreazza Araújo; Filho, José Ferreira; Cabral, Augusto César de Aquino; Santos, Sandra Maria dos; Pessoa, Maria Naiúla Monteiro (Revista de Administração da UFSM, 2015)
The article aims at investigating the relationship between management practices implemented by Embracon – Brazilian Company Consortium, in Fortaleza, Ceará, to build shared vision and the organizational commitment. The case study was conducted using the qualitative method, a descriptive, survey data with secondary internal company documents, and application of semi-structured interviews for data collection from the perspective of unit managers. It was observed that the company adopts practices to develop shared vision. The managers had shown a great level of satisfaction and affective commitment as well as their team. There is also a strong and direct relationship between the CEO and all employees of the organization. There is also a prevailing bond of affection between the employees and the employer. The company has a personal meaning for the employees and most of them intend to keep working there until retirement, thus presenting a great level of commitment.